2020
DOI: 10.3390/coatings10080716
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Surface Integrity of Q345 Steel After Nd:YAG Laser Cleaning of Oxidized Mining Parts

Abstract: As a common mechanical material for mining machinery, Q345 is prone to oxidation due to the moist working environment. At present, laser cleaning is often used to remove rust oxides from the substrate. The pollutant of mining machinery is comprised of a heavy oxide layer and organic ingredients, which are difficult to remove and require high energy per pulse. However, excessive energy is capable of easily destroying surface integrity, such as increasing surface roughness (Ra), generating ablative pits, oxidizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Zhang et al [12] identified that at low energy densities, the primary mechanism of laser cleaning of metal oxides is ablation, where high-energy pulsed lasers not only cause phase explosion but also facilitate oxide layer removal through pressure-induced shock effects. Ma et al [13] employed a fiber laser to remove rust oxides from Q345 steel commonly used in the mining industry and explored the surface integrity at different laser powers to determine the optimum cleaning parameters and confirm the feasibility of laser cleaning. Xing et al [9] investigated rusty steel using a combination of molten salt pretreatment and laser cleaning, noting an enhanced ease of rust layer removal at lower laser irradiation intensities.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [12] identified that at low energy densities, the primary mechanism of laser cleaning of metal oxides is ablation, where high-energy pulsed lasers not only cause phase explosion but also facilitate oxide layer removal through pressure-induced shock effects. Ma et al [13] employed a fiber laser to remove rust oxides from Q345 steel commonly used in the mining industry and explored the surface integrity at different laser powers to determine the optimum cleaning parameters and confirm the feasibility of laser cleaning. Xing et al [9] investigated rusty steel using a combination of molten salt pretreatment and laser cleaning, noting an enhanced ease of rust layer removal at lower laser irradiation intensities.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the authors propose solutions to modernize the mechanical units and structural parts, which can reduce the negative impact of the new operating conditions on the mining machine [11]. There are numerous studies on the behaviour of this mechanical material frequently used in the construction of the component parts of mining equipment [1][2][3], the failure behavior and the degree of wear of the component material of the load-bearing structure of heavy machinery [5], deformation characteristics [9], the stresses applied to some component parts of the excavators [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As industrial demand grows, research on the process parameters, surface quality, and performance of laser cleaning is expanding. For example, Ma et al [10] conducted single-factor experiments to investigate the effects of laser cleaning on the rust layer of Q345 steel used in mining machinery. They specifically examined the influences of laser power and spot overlap rate on the post-cleaning surface integrity, ultimately determining optimal cleaning process parameters.…”
Section: Introductionmentioning
confidence: 99%